The secretome of skeletal muscle cells: A systematic review - Florin, Antoine; Lambert, Cécile; Sanchez, Christelle; Zappia, Jérémie; Durieux, Nancy; Tieppo, Antonio Martins; Mobasheri, Ali; Henrotin, Yves (Osteoarthritis and cartilage open, 2020)
Proteomic studies of the secretome of skeletal muscle cells can help us understand the processes that govern the synthesis, systemic interactions and organization of skeletal muscle and identify proteins that are involved in muscular adaptations to exercise, ageing and degeneration. In this systematic review, we aimed to summarize recent mass-spectrometry based proteomics discoveries on the secretome of skeletal muscle cells in response to disease, exercise or metabolic stress. A literature search was performed in the Medline/Ovid and Scopus electronic bibliographic databases. Only papers reporting the analysis of the secretome by mass spectrometry were included. A total of 19 papers met the inclusion criteria for this systematic review. These papers included comparative analysis of differentially expressed proteins between healthy and unhealthy muscle cells and comparison of the secretome of skeletal muscle cells during myogenesis and after insulin stimulation or exercising. The proteins were separated into several categories and their differential secretion was compared. In total, 654 proteins were listed as being present in the secretome of muscle cells. Among them, 30 proteins were differentially regulated by physical exercise, 130 during myogenesis, 114 by dystrophin deficiency, 26 by muscle atrophy, 27 by insulin stimulation and finally 176 proteins secreted by insulin-resistant muscle cells. This systematic review of the secretome of skeletal muscle cell in health and disease provides a comprehensive overview of the most regulated proteins in pathological or physiological conditions. These proteins might be therapeutic targets or biochemical markers of muscle diseases.